Efeito comparativo da curcumina in natura e da nanopartícula de curcumina sobre a resposta inflamatória experimental - Rocha, Bruno Ambrósio da (2014)
Curcuma longa L., commonly known as turmeric, has been used to treat some diseases such as gastric ulcers, infections of skin and eyes, and rheumatoid arthritis. Studies show that curcumin (Cur) has low water solubility and impaired bioavailability as a consequence of poor absorption, rapid hepatic and intestinal metabolism and also systemic elimination, justifying the development of new formulations that allow the improvement of its bioavailability. The aim of this study was compared the effect of Cur and nanocoated curcumin (CurNano) on acute inflammatory response in mice. It was used technique miniemulsificação/solvent evaporation to obtain nanoparticles of poly (L- lactic acid) containing curcumin at different concentrations (1%, 3%, 9%, 15%). The results demonstrated a high encapsulation efficiency for all concentrations tested, however, the analyzes Recovery, Scanning Electron Microscopy, Calorimetry and Infrared indicated that the formulation containing 3% curcumin obtained the best results. Biological evaluation were used the experimental models of paw edema induced by carrageenan and dextran. The treatment of mice was carried orally in a single dose daily with Cur and CurNano at doses of 50, 100, 200 and 400 mg/Kg and 25 and 50 mg/Kg, respectively. The results showed that treatment with CurNano in dose 8-fold smaller than Cur, obtained similar inhibitory effects on the development of paw edema, reduce myeloperoxidase activity and the concentration of nitric oxide in plant tissue. Thus, the data provide evidence that the processo of nanoencapsulation improved the bioavailabity of curcumin.